Predictors of physical inactivity among antenatal women: a systematic review - Mohamad Yusof, Nazatul Yusrina; Mohd Zulkefli, Nor Afiah; Minhat, Halimatus Sakdiah; Ahmad, Norliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
The American College of Obstetricians and Gynaecologists (ACOG), US Department of Health and Human Services (HHS), and American College of Sports Medicine (ACSM) recommend that all pregnancies with medical clearance should engage in moderate-intensity physical activity (PA) at least 150 minutes per week. However, most of them are physically inactive. Thus, this article aims to identify predictors of physical inactivity among antenatal women. Four databases were used to search relevant articles using PICO strategy systematically. The screening began with examining titles, abstracts, and keywords, followed by scrutinizing and assessing full articles. Finally, a total of five studies were included for the data extraction, and the predictors are sociodemographic (trimesters, parity, marital status, and pre-pregnancy PA status), socioeconomic (household income), lifestyle (smoking and eating unhealthy diet) and health-related factors (multiple pregnancies, received fertility treatment, being unwell, musculoskeletal pain, symptom of early pregnancy and uterine contraction). All these predictors provide crucial information for the success of future physical activity intervention.